jwilson.coe.uga.edu/EMT668/EMAT6680.Folders/Barron/unit/Lesson 5/5.html

Specifically, we graphed the two equations y = 2x + 5 and y = (-3/2)x + 2, and ...
Now, we can set the right hand side of each equation equal to each other
because they both equal y. ... x = 5y in the second equation, then x must also
equal 5y in the first equation. .... Also, the point (0, 19/14) works, where x = 0 and
y = 19/14.

www.montereyinstitute.org/courses/Algebra1/COURSE_TEXT_RESOURCE/U04_L1_T2_text_final.html

We can use the characteristics of intercepts to quickly calculate them from the
equation of a line. ... To find the y-intercept, we substitute 0 for x in the equation,
because we ... Example. Problem. 3y + 2x. = 6. 3y + 2(0). = 6. 3y. = 6. = Answer. y.
= 2 ... a line—we just have to plot the intercepts and then draw a line through
them...

www.columbia.edu/itc/sipa/math/systems_linear.html

By setting first x and then y equal to zero it is possible to find the y intercept on ...
If x = 0, then f(0) = 1 + .5(0) = 1. If y = 0, then f(x) = 0 = 1 + .5x. -.5x = 1. x = -2 ... If y
= 0, then f(x) = 0 = 11 - 2x. 2x = 11. x = 5.5. The resulting data points are (0,11)
and (5.5,0) ... From the graph it can be seen that these equation...

www.purplemath.com/modules/syseqgen4.htm

As before, I'll set these equations equal, and solve for the values of x: ... Since the
first equation is already solved for y, I will plug "–x – 3" in for "y" in the second
equation, and solve ... y = (<sup>1</sup>/2)x – 5 = (<sup>1</sup>/2)(<sup>5</sup>/2) – 5 = <sup>5</sup>/4 – <sup>20</sup>/4 = – <sup>15</sup>/4 = –3.75
... y = –x + 2. Then: xy = 1 x(–x + 2) = 1 –x<sup>2</sup> + 2x = ...

www.themathpage.com/alg/equation-of-a-line-2.htm

How to find the x- and y-intercepts of the graph of a straight line. ... Calculate the
value of x when y = 0, that is, find the x-intercept of y = 2x + 10. Solution. ... 2x +
10, = 0. We have: 2x, = −10. x, = −5. ... a) When we have the equation of a straight
line, how do we find the ... Find the intercepts by putting x -- then y -- equ...

www.rasmus.is/uk/t/F/Su52k03.htm

How do we set about finding the points in which two graphs y = f(x) and y = g(x)
intersect? ... We calculate it by solving the equation f(x) = 0 . ... Solve the equation
x<sup>2</sup> − 2x − 3 = 2x − 3 first graphically, then algebraically. ... Example 5 ... definition
of a logarithm we can see that x = 1 makes both sides of the equation equal to ...

www.khanacademy.org/math/cc-eighth-grade-math/cc-8th-linear-equations-functions/8th-x-and-y-intercepts/v/x-and-y-intercepts-2

Sal finds the x and y-intercepts of the equation 2y + 1/3x = 12. ... So let's set each
of these values to 0 and then solve for what the other one has to be at that point.
So for the x-intercept, when y is equal to 0, let's solve this. So we get ... I'll just do
a little hand-drawn graph, and make it clear what the x- and the...

www.analyzemath.com/math_questions/math_questions_2_sol.html

... then f <sup>-1</sup>(x) = Solution y = Log(x) if and only if x = 10 <sup>y</sup>. Interchange x and y y =
10 <sup>x</sup>. Hence ... Hence their exponents has also to be equal 3x - 1 = 4. Solve for x
x = 5/3 ... The roots of the equation x / (x + 2) + 3 / (x - 4) = (4x + 2) / (x <sup>2</sup> - 2x - 8)
are .... If Pi < x < 3 Pi/2, then sin(x) can be expressed in terms of...

www.math.ucdavis.edu/~kouba/CalcOneDIRECTORY/implicitdiffsol2directory/ImplicitDiffSol2.html

2x + ( xy' + (1)y ) + 2 y y' = 0 , ... To find y'' , differentiate both sides of this equation,
getting .... If the first derivative y' does not exist, then the denominator in Equation
1 equals zero ... If x=0 in the original equation (x<sup>2</sup>+y<sup>2</sup>)<sup>2</sup> = 2x<sup>2</sup>-2y<sup>2</sup> , then.

www.analyzemath.com/math_questions/math_questions_1_sol.html

If Log x (1 / 8) = - 3 / 2, then x is equal to ... If the graph of f is a parabola with
vertex on x axis and opening up, then the range of f is given by the interval ...
When a parabola represented by the equation y - 2x <sup>2</sup> = 8 x + 5 is translated 3
units ... sin(0) = 0 and cos(0) = 1, and from x = 0 to x = pi/2, sin(x) increases from 0 ...